Synthesis of N-Glycosyl Amides via Hydrolysis of Protected Glycosyl Oxazolines and Ritter-like Reactions of Native Carbohydrates - Grigorii, G. Sivets (Journal of New Developments in Chemistry, 2025)
A stereoselective synthesis of N-glycosyl amides was studied from available N-glycosyl oxazolines prepared by Ritter-like reactions of protected sugar acetonides. Hydrolysis reactions of the protected pentofuranosyl and hexafuranosyl oxazolines, as precursors of glycosyl amine derivatives, were carried out in the presence of silica gel in chloroform to giveN-α- and β-glycosyl amides in good yields after column chromatography on silica gel. Access to selectively blocked N-α-xylo-, -ribo-, β-arabino-furanosyl, α-glyco-, α-allo-furanosyl, α- and β-galactopyranosyl amides (twelve examples) useful for preparing modified N-glycosides was accomplished through a mild hydrolysis of sugar oxazolines with 2-alkyl substituents in acidic and neutral conditions. To further explore the scope of the BF3.Et2O-mediated approachdeveloped for N-furanosyl oxazolines, a stereoselective synthesis of protected N-α-hexopyranosyl oxazoline was fulfilled in a high yield from d-galactopyranose diacetonide derivative. The Ritter-like promoted reaction between D-arabinose and benzonitrile afforded 2-phenyl-β-d-arabinofurano-(1,2-d)-2-oxazoline as the main product. In acetonitrile the BF3.Et2O-KHF2-assisted reactions of unprotected native sugars were found to result in the formation of mixtures of N-furanosyl and pyranosyl acetamides.
Keywords: N-glycosyl oxazolines; hydrolysis reactions on silica gel; N-glycosyl amides; Ritter-like reactions; nitriles; unprotected carbohydrates